Reinterpreting The Concept of Shari’ah and Its Implication on Gender Issues - Najib, Agus Moh. (UIN Sunan Kalijaga, 2008)
This paper deals with Mahmoud Mohamed Taha’sthought on shari’ah and gender. The main message conveyed byshari’ah is equality between man and woman with the aim ofachieving gender justice in society. Many Muslim scholars,however, interpret shari’ah text written in the Qur`an and theSunnah textually, partially and out of its context. Suchinterpretation then produce gender biased understandings andunequal gender rulings. This paper analyze how Mahmoudinterprets the concept of shari’ah and implements it on genderissues. Different from many Muslim scholars, Mahmoud views thatshari’ah evolves continuously in the history of human beings and itis showed by the presence of different shari’ahs from one prophetto another, from Adam until Mohamed (peace be upon them).Because of its characteristic, the last shari’ah brought by Mohamedalso must evolve, namely, evolving from the subsidiary verses ofthe Qur`an to its primary verses. In this way, shari’ah rules whichcontain gender discriminations are regarded as transitional rulessuiting the social context at the time. In the contemporary era, therelation between men and women must be based on the primaryverses of the Qur`an which emphasize the principles of genderequality.